Analyse De La Performance Productive De L’agriculture Urbaine Dans Le District d’Abidjan - Kouakou Kouakou Paul-Alfred (European Scientific Journal, ESJ, 2017)
Rapid population growth observed in the Cote d’Ivoire is associated with rapid urbanization. This urban growth results in demand growth in food products. In this context, the Urban Agriculture for its specialization in production of fruits and vegetables generate a lot of interest. The purpose of this study is then to assess the performance of this agriculture and identify potential determinants of its technical efficiency. The estimate of the production frontier has found that the technical efficiency of producers is between 21% and 97% with an average technical efficiency of 76%. The analysis of the determinants of the efficiency showed that the legal status of the occupied space, the level of education, the quality of irrigation water, the access to credit and the nature of the main activity impact significantly on the technical efficiency. The improving of urban farmers’ efficiency means strengthening training and technical support to producers for rational use of space and practices and by integrating this type of activity in development plans of this district.